VD_FINDINFO Jug / 2023 / 226 vom 30. Mai 2022 - VD Tribunal cantonal (2022)
CHANTAGE, TENTATIVEDROIT PÉNAL, INSTIGATION, ESCROQUERIE, PAR MÉTIER, FIXATION DE LA PEINE | 22 ad 156 ch. 1 CP, 24 CP, 303 ch. 1 CP, 47 CP, 49 al. 1 CP